Agricultural production and nutrition implications in Cambodia - Phearun, Heng (WorldFish, 2024)
Agriculture is a key sector in Cambodia, accounting for 22% of GDP in 2022, with 57% of households engaged in agricultural production. The vast majority of these households (94%) are involved in crop cultivation, primarily non-aromatic paddy rice, followed by mango and banana crops. Livestock and poultry farming are also significant, with 82% of farmers participating. However, aquaculture is practiced by only 6% of agricultural households. The sector remains vital for food security, despite its declining share in GDP because of structural changes in the economy. This study focuses on five provinces, examining household agricultural activities, including crop cultivation, livestock management, and aquaculture, based on a survey conducted in mid-2023. The objective is to comprehensively assess the productivity of agricultural households in Cambodia and to evaluate the nutrient content produced by their agricultural outputs.